Selection of Plate Components of Operator’s Cabin Walls in Aspect of Thermal Insulation and Transmission Loss - DZIECHCIOWSKI, Zygmunt (Archives of Acoustics, 2011)
The modern cabin of heavy duty machines have to fulfil a number of requirementswhich deal with operators’ work comfort. More and more often, the vibroacousticand thermal comforts decide about the cabin quality. This paper presents principlesof acoustic and thermal calculations as well as their use in combined assessment.